Математичне моделювання процесу облаштування внутрішніх приміщень цивільних споруд - Коваль, В. Б. (Ways to Improve Construction Efficiency, 2014)
With the help of mathematical modeling based on the algorithm "greed" Charge the device interior partitions by the criterion of a minimum price. It was found that this criterion corresponds to the device interior partitions of innovative energy-efficient and environmental building material - aerated concrete. Calculations show that through the use of innovative materials - aerated concrete, at constant values of C and n at duration of works on arrangement of interior partitions is 5.5 days, which is in the 1.1-1.6 times smaller partitions everything from traditional materials - brick and gypsum blocks.